Family firms and debt: Risk aversion versus risk of losing control (2011)
This study examines the effect of family management, ownership, and control on capital structure for 523 listed and unlisted Colombian firms between 1996 and 2006 (5,094 firm-year observations). The study finds that when families are involved in management, debt levels tend to be lower for younger firms when the founder is still present or when heirs act as managers, but trends heighten as the firm ages. When families' involvement derives from direct and indirect ownership, the family/debt relationship is positive; consistent with the idea that external supervision accompanies higher debt levels and reduces the risk of losing control. When families are present on the board of directors (but are not in management), debt levels tend to be lower, suggesting that family directors are more risk-averse. The results stress the tradeoff between two distinct motivations that determine the capital structure of family firms: Risk aversion pushes firms toward lower debt levels, but the need to finance growth and the risk of losing control make family firms prefer higher debt levels.